2021
DOI: 10.3389/fcell.2021.726323
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell-Derived Exosomal Circ-0072088 Suppresses Migration and Invasion of Hepatic Carcinoma Cells Through Regulating MMP-16

Abstract: Background: Tumor-derived exosomes (EXOs), commonly differentially expressed in circular RNAs, have been shown to be crucial determinants of tumor progression and may regulate the development and metastasis of hepatic carcinoma (HCC).Methods: Possibly differentially expressed circRNAs in patients with HCC were screened out from the Gene Expression Omnibus (GEO). EXOs were isolated from the culture medium of HCC cells and plasma of patients with HCC, followed by characterization by transmission electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Previous studies suggested that circRNAs primarily function as miRNA sponges to regulate gene expression ( Huang et al, 2020 ; Lin et al, 2021 ; Ren et al, 2021 ). By bioinformatics prediction, we identified miR-545-3p as the common target of circFGGY and Smad7.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that circRNAs primarily function as miRNA sponges to regulate gene expression ( Huang et al, 2020 ; Lin et al, 2021 ; Ren et al, 2021 ). By bioinformatics prediction, we identified miR-545-3p as the common target of circFGGY and Smad7.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Lin et al. ( 40 ) found a notably decreased 5-year survival rate in those with high circ-0072088. The results indicated that high expression of circ-0072088 was closely correlated with an unfavorable prognosis and may be involved in the development of HCC.…”
Section: The Diagnostic and Prognostic Values Of Exosomal Circrnas In...mentioning
confidence: 99%
“…In another study, the expressions of exosomal circ-0072088, circANTXR1, circTMEM45A, hsa_circ_0061395, and hsa_circ_0004001 were significantly upregulated in patients with HCC and positively correlated with TNM stages and tumor size but not with gender or age. In addition, the expression of circTMEM45A was also related to vascular invasion ( 40 , 42 , 45 , 47 , 56 ). Furthermore, high levels of hsa_circ_0004123 and hsa_circ_0075792 expression were positively correlated with tumor size and the TNM stages, but not with age, gender, and LNM ( 56 ).…”
Section: Relationships Between Exosomal Circrnas and Clinicopathologi...mentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Through bioinformatic analysis and literature reviews, [13][14][15] the consistent upregulation of circ 0072088 expression in LUAD has persuaded us to further examine its role. Paradoxically, some reports have shown that the downregulation of circ 0072088 in hepatic carcinoma cells derived exosome is associated with tumorigenesis, 16 similarly, its decrease has been reported to be associated with metastasis of colorectal cancer, 17 suggesting that, it is necessary to further explore the expression and function of circ 0072088 in the mechanisms underlying LUAD.…”
Section: Introductionmentioning
confidence: 99%